2022
DOI: 10.1038/s41394-022-00552-4
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of home hand rehabilitation using musicglove after chronic spinal cord injury

Abstract: Study design Randomized, controlled single-blind cross over study. This study was registered on ClinicalTrials.gov (NCT02473614). Objectives Examine usership patterns and feasibility of MusicGlove for at home hand rehabilitation therapy following chronic spinal cord injury. Setting Homes of participants. Methods Ten participants with chronic spinal cord in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(28 citation statements)
references
References 43 publications
0
28
0
Order By: Relevance
“…The main objective is to hit as many notes as possible. The difficulty level of each song is tailored to accommodate various degrees of hand impairment, aligning with the individual’s skill level Effectively measures hand dexterity (% of correctly hit notes), showing a strong correlation with the BB score Incorporation of music into training sessions leads to significant improvements in both objective measures of hand motor performance and motivation Friedman et al [ 50 ] 2014 Participants improved hand function, particularly in grasping small objects, compared to conventional methods (BB score and 9 Hole Peg test) Strong correlations were found with the BB score Reported as more motivating than the conventional therapy Sanders et al [ 48 ] 2020 Amount of practice was not correlated with the average level of success experienced, but it was correlated with the amount of parameter exploration (hours of use) and completed grips were comparable to individuals in the chronic phase of stroke in a previous study [ 53 ] Feasible for autonomous home use and caused no adverse effects Sanders et al [ 49 ] 2022 Participants demonstrated higher compliance levels (hours of use and completed more grips) compared to individuals in previous stroke studies utilizing the same device Notable improvements in prehension ability and performance (Graded and Redefined Assessment of Strength, Sensibility, and Prehension subtests) Increased performance on the BB test compared to the conventional group Zondervan et al [ 51 ] 2016 Participants exhibited significantly greater enhancements in Motor Activity Log quality of movement and amount of use MusicGlove and conventional exercise groups significantly improved Box and Blocks test scores with no notable difference Adamovich et al [ 54 ] 2009 This study introduces a robotic/virtual environment dedicated to improving hand and arm coordination by simulating a piano with realistic visual, auditory, and tactile feedback. Enabling users to train both arms and hands concurrently, an algorithm dynamically adjusts task difficulty based on individual performance.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The main objective is to hit as many notes as possible. The difficulty level of each song is tailored to accommodate various degrees of hand impairment, aligning with the individual’s skill level Effectively measures hand dexterity (% of correctly hit notes), showing a strong correlation with the BB score Incorporation of music into training sessions leads to significant improvements in both objective measures of hand motor performance and motivation Friedman et al [ 50 ] 2014 Participants improved hand function, particularly in grasping small objects, compared to conventional methods (BB score and 9 Hole Peg test) Strong correlations were found with the BB score Reported as more motivating than the conventional therapy Sanders et al [ 48 ] 2020 Amount of practice was not correlated with the average level of success experienced, but it was correlated with the amount of parameter exploration (hours of use) and completed grips were comparable to individuals in the chronic phase of stroke in a previous study [ 53 ] Feasible for autonomous home use and caused no adverse effects Sanders et al [ 49 ] 2022 Participants demonstrated higher compliance levels (hours of use and completed more grips) compared to individuals in previous stroke studies utilizing the same device Notable improvements in prehension ability and performance (Graded and Redefined Assessment of Strength, Sensibility, and Prehension subtests) Increased performance on the BB test compared to the conventional group Zondervan et al [ 51 ] 2016 Participants exhibited significantly greater enhancements in Motor Activity Log quality of movement and amount of use MusicGlove and conventional exercise groups significantly improved Box and Blocks test scores with no notable difference Adamovich et al [ 54 ] 2009 This study introduces a robotic/virtual environment dedicated to improving hand and arm coordination by simulating a piano with realistic visual, auditory, and tactile feedback. Enabling users to train both arms and hands concurrently, an algorithm dynamically adjusts task difficulty based on individual performance.…”
Section: Resultsmentioning
confidence: 99%
“…Among these, ten studies exclusively involved participants with neurological disorders (PwND). Specifically SCI [ 49 ] and stroke [ 48 , 50 , 51 , 53 , 54 , 59 , 60 , 62 , 63 ]. Conversely, five studies, which were conference articles, exclusively enrolled participants without neurological disorders (PwoND).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the past few years, passive and active rehabilitation therapies with wearable devices have been successfully used to improve muscle activity [5]. Sensor-based devices are a critical component of finger active rehabilitation systems, and they are used for sensing and measuring different movements in a human fingers [6]. In general, measuring hand and finger movements and muscle strength requires flexible, multi-functional sensors.…”
Section: Introductionmentioning
confidence: 99%